Stochastic efficiency of thermodiffusion: an extended local equilibrium approach. (14th March 2019) - Derivaux, Jean-François; De Decker, Yannick
Abstract: The recently established connection between stochastic thermodynamics and fluctuating hydrodynamics is applied to a study of efficiencies in the coupled transport of heat and matter on a small scale. A stochastic model for a mesoscopic cell connected to two macroscopic reservoirs of heat and particles is developed, based on fluctuating hydrodynamics. Within this approach, the fluctuating separation and thermodynamic efficiencies are defined. The conditions required to observe bimodal distributions of these efficiencies are determined, and the evolution of these distributions is investigated in the large-size and in the long-time limits. The results obtained are not restricted to thermodiffusion and can be generalized to systems where efficiency is defined as a ratio of stochastic state variables or dissipation rates.